2018
DOI: 10.1073/pnas.1719267115
|View full text |Cite
|
Sign up to set email alerts
|

Human hydroxymethylbilane synthase: Molecular dynamics of the pyrrole chain elongation identifies step-specific residues that cause AIP

Abstract: Hydroxymethylbilane synthase (HMBS), the third enzyme in the heme biosynthetic pathway, catalyzes the head-to-tail condensation of four molecules of porphobilinogen (PBG) to form the linear tetrapyrrole 1-hydroxymethylbilane (HMB). Mutations in human () cause acute intermittent porphyria (AIP), an autosomal-dominant disorder characterized by life-threatening neurovisceral attacks. Although the 3D structure of hHMBS has been reported, the mechanism of the stepwise polymerization of four PBG molecules to form HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 39 publications
5
65
1
Order By: Relevance
“…Prokaryotic expression studies revealed that this change produces a protein with little, if any, residual activity. A previously identified disease-causing mutation at the same residue (p.K98R) had a similar activity when expressed in E coli [3,20].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Prokaryotic expression studies revealed that this change produces a protein with little, if any, residual activity. A previously identified disease-causing mutation at the same residue (p.K98R) had a similar activity when expressed in E coli [3,20].…”
Section: Discussionmentioning
confidence: 72%
“…The novel missense mutation p.K98N affects a residue that is invariant through evolution [2,3]. Lysine 98 is part of domain 1 of HMBS and interacts with the dipyrromethene cofactor at the active site [3]. Prokaryotic expression studies revealed that this change produces a protein with little, if any, residual activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pyrrole elongation ( Figure 3 ) is a stepwise condensation, which starts from a dipyrromethane (DPM) cofactor in the holoenzyme (E), creating enzyme-intermediate complexes bound to one, two or three PBG molecules, referred to as ES, ES 2 and ES 3 . In the last step, an enzyme-intermediate complex bound to four PBG molecules is generated, i.e., ES 4 , and quickly released from the cofactor by hydrolysis yielding the linear HMB, as reviewed by Bung et al [ 62 ]. The DPM cofactor, composed of two PBG molecules, is not incorporated in the product and remains covalently attached to the enzyme [ 63 , 64 ].…”
Section: Introductionmentioning
confidence: 99%